PENGARUH EFEKTIVAS PENGELOLAAN DANA DESA TERHADAP PEMBERDAYAAN MASYARAKAT DI KECAMATAN TELUKNAGA KABUPATEN TANGERANG - Siti Wahyuni Ramadhani; Achmad Murodi; Hari Muljono (UNIVERSITAS ISLAM SYEKH YUSUF, 2019)
The title of this thesis is “The Influence of Effectiveness of Village Fund Management of Community Empowerment in Teluknaga sub-district of Tangerang Regency”. The method used in this research is a quantitative method. In determining the sample size of researchers using the technique of Quota Sampling (Sugiyono 2016: 85). Where the technique used to determine samples from populations that have certain characteristics to the desired amount. The samples are the community that has the characteristics of following a community empowerment program held in each village where they live which is located in three villages in the sub-district of Teluknaga Tangerang Regency. In the data collection, the research uses the dissemination of adoptive instruments, interview and observations. The analysis technique used in this research is quantitative analysis method is research conducted by collecting answers from respondents or questions that are the measurements of the variables studied. Then the data obtained were analyzed using SPSS (Statistical Product and Solution Services) for windows version 24 using correlation techniques using the method person product moment according to Sugiyono and continued regression testing.Keywords : Effectiveness, Village Fund, Community Empowerment